A low complexity distributed differential scheme based on orthogonal space time block coding for decode-and-forward wireless relay networks - Samer Alabed; Nour Mostafa; Wael Hosny Fouad Aly; Mohammad Al-Rabayah (International Journal of Electrical and Computer Engineering (IJECE), 2023)
This work proposes a new differential cooperative diversity scheme with high data rate and low decoding complexity using the decode-and-forward protocol. The proposed model does not require either differential encoding or channel state information at the source node, relay nodes, or destination node where the data sequence is directly transmitted and the differential detection method is applied at the relay nodes and the destination node. The proposed technique enjoys a low encoding and decoding complexity at the source node, the relay nodes, and the destination node. Furthermore, the performance of the proposed strategy is analyzed by computer simulations in quasi-static Rayleigh fading channel and using the decode-and-forward protocol. The simulation results show that the proposed differential technique outperforms the corresponding reference strategies.